Optimal DNA quality preservation process for comprehensive genomic testing of pediatric clinical autopsy formalin-fixed, paraffin-embedded tissues - Noriko Watanabe; Tomohiro Umezu; Masashi Kyushiki; Kayoko Ichimura; Atsuko Nakazawa; Masahiko Kuroda (Polish Journal of Pathology, 2023)
Clinical autopsies are performed to reveal the process of the disease that caused patient death and validate the diagnosis and treatment decisions. In pediatric clinical autopsy, the feedback provided to bereaved families has a considerable social impact; however, pediatric diseases are diverse, which makes it difficult to elucidate them. Therefore, it is necessary to employ molecular biology techniques in addition to conventional methods. Formalin-fixed, paraffin-embedded (FFPE) tissues are routinely prepared. However, clinical autopsy FFPE tissue processing is not standardized, and it is unclear whether DNA from such tissues can be used for comprehensive genomic analysis. In this study, we evaluated the DNA quality of FFPE tissues from 15 recent autopsy cases at a single-center children’s hospital using quantitative polymerase chain reaction [PCR (Q129/Q41)] and nanoelectrophoresis (DNA integrity number (DIN)). Good quality DNA was obtained from every organ type excluding bone marrow within 6 days of formalin fixation. Prolonged proteinase K digestion (48 h > 24 h > 1 h) and thicker tissue sections (10 µm > 1 µm) improved Q129/Q41; however, 24 h fixed FFPE tissues showed better DNA quality. We propose an optimal and feasible workflow for storing short-term fixed FFPE tissues as DNA-preserved FFPE tissues for future comprehensive genomic searches.